Aspectos florísticos de Lacanhá Chansayab, Selva Lacandona, Chiapas - Levy Tacher, Samuel I.; Aguirre Rivera, J. Rogelio; García Perez, José D.; Martínez Romero, María Magdalena (Instituto de Ecología, A.C., 2006)
A systematic sampling of the flora was carried out between 1993 and 1999 in several evergreen tropical rainforest stands, “acahuales” (local name for old agricultural fields) of various ages and agricultural fields belonging to the Lacanhá Chansayab community, located at the Lacandonian tropical rainforest. Collected individuals were identified and processed as herbarium specimens, including information on life form, phenology and status of conservation. Four hundred and eighty five vascular plant species were recorded, corresponding to 355 genera from 104 families, which represent 11.23% of all species estimated for the area. Fabaceae, Asteraceae and Rubiaceae were the best represented families, as well as the genera Piper, Eupatorium, Encyclia, Chamaedorea and Solanum.